If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -9 = 12y + 47 Reorder the terms: -9 + 4y = 12y + 47 Reorder the terms: -9 + 4y = 47 + 12y Solving -9 + 4y = 47 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -9 + 4y + -12y = 47 + 12y + -12y Combine like terms: 4y + -12y = -8y -9 + -8y = 47 + 12y + -12y Combine like terms: 12y + -12y = 0 -9 + -8y = 47 + 0 -9 + -8y = 47 Add '9' to each side of the equation. -9 + 9 + -8y = 47 + 9 Combine like terms: -9 + 9 = 0 0 + -8y = 47 + 9 -8y = 47 + 9 Combine like terms: 47 + 9 = 56 -8y = 56 Divide each side by '-8'. y = -7 Simplifying y = -7
| f(x)=x^2+8x-12 | | 5(x-3)=2x+9 | | 6-7/4x8 | | 27x-3x^3=0 | | -x*2x=64 | | -2x^2=-124 | | Cd+de= | | 12x+14=62 | | 3(6x-4)=21 | | 5st+6su-4sv= | | ysquared=17y-72 | | n^3+216m^3=0 | | -4/5x=-33.52 | | 2511=a*461*294 | | x+103+2x+77=180 | | 5x-3+20x+8=180 | | 30+1=13 | | 2=a*2*2 | | 12g+35= | | F(t)=-3t^4+3t^2-2t+1 | | 5(x+9)=8(x-6) | | |x|= | | 36x+2=110 | | 5t-whent=-4 | | 139=17x+3 | | 141/2?= | | -2cos^2x-5cos+3=0 | | 141/2= | | 4(3x+6)=15x-8+4x | | 5y+4=5y+5 | | -x/3=1/8 | | 6m-3=27 |